Gimnasia aeróbica y su incidencia en la calidad de vida de los habitantes del sector “el Malecón” del cantón Baquerizo Moreno, provincia del Guayas - Bajaña Franco, Rita Eufemia (2018)
The work titled Aerobic Gymnastics and its impact on the quality of life of the inhabitants of the sector "the pier" Baquerizo Moreno, collects diagnostic results that reveal the situation presented by people in the sector with problems in their quality of life and ignorance of the risks that represent not devoting a space of time to perform physical physics for health, the explorers made possible to know the activities carried out by the people under study and their knowledge about the quality of life, as well as the predisposition on the part of of the neighborhood leaders to support proposals for physical activity that can contribute to the improvement and maintenance of the health status of the residents of their sector. Methods of the theoretical level and the empirical level of scientific research were used, as well as mathematical methods and statistics. It is the opinion of this author that the industrial result obtained, to be taken into account by the relevant authorities, can contribute to raising the quality of life of the inhabitants of the sector of the Baquerizo Moreno waterfront.